Rupture of non-communicating horn of a bicornuate uterus - Mishra, Jagannath; Rout, Subhashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A primigravida at 20 weeks GA was referred as a case of bleeding P/V with an USG report showing intra-uterine foetal demise. Accordingly we induce her with misoprostol followed by ethacrydine lactate but there was no progress. On repeat USG here we saw there was rupture of a horn of uterus with abortus free in peritoneal cavity. On laparotomy there was 1 litre of hemoperitoneum with abortus lying free inside. There was rupture of a non-commnicating horn of a bicornuate uterus which was excised and uterine wall repaired.